Manajemen Kurikulum dalam Meningkatkan Mutu Pendidikan di MTsN 6 Tanah Datar - Dini Febriyenti; Jamilus Jamilus; Winda Martavia; Asmendri Asmendri (UIN Mahmud Yunus Batusangkar, 2022)
This study aims to describe the curriculum management process in improving the quality of education at MTsN 6 Tanah Datar. This research was conducted using a qualitative descriptive research method. Sources of data in this study were principals, representatives of the curriculum and teachers. Data collection techniques in this study were conducted by means of interviews, documentation. The data analysis technique used in this research is data reduction, data presentation and conclusion drawing. The results obtained are that curriculum planning is carried out through workshop activities held at the beginning of the new school year as an effort to implement the curriculum that will be applied in the next academic year, then the implementation of the curriculum is seen from the distribution of local content and subjects as well as the ongoing education process in one year. of the teaching, curriculum evaluation is carried out in workshop activities along with the curriculum planning process and learning process for the next academic year. Curriculum evaluation also looks at student achievement to improve the quality of educationÂ Keywords: Curriculum Management, Education Quality